The Influence of Professional Identity and Resilience on Turnover Intention Among Startup Employees at PT XYZ: The Mediating Role of Job Satisfaction, Work Engagement, and Burnout - Pranata, Agus Adi; Ardi Ardi; Richard Andre Sunarjo (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study examines the influence of professional identity and resilience on employees' intentions to leave their jobs, focusing specifically on employees at PT XYZ, an early-stage startup. Job satisfaction, work engagement, and burnout serve as hypothesized mediating variables, playing a crucial role in determining the relationship between professional identity, resilience, and turnover intention. The aim of this research is to explore how each of these psychological constructs impacts turnover intention, particularly within a startup context where employee retention poses a significant challenge. Using a quantitative approach, data were collected through structured questionnaires completed by PT XYZ employees. The analysis results show that professional identity and resilience significantly contribute to increased job satisfaction and work engagement, as well as decreased burnout levels, which subsequently lower employees' turnover intentions. These findings offer practical implications for startup management in retaining employees, including strengthening professional identity, fostering resilience through targeted training, and providing equitable compensation. These recommendations are expected to help startups enhance employee retention, as workforce sustainability remains a critical factor for growth during the early stages of a company’s development.